Pelatihan Teknologi Air Conditioning System Di Lingkungan Bandar Udara - Asep Muhammad Soleh; Viktor Suryan; Catra Indra Cahyadi; Direstu Amalia; Virma Septiani; Randa Agusta Pratama; Muhammad Rafli Fazal (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2022)
Lack of knowledge of technicians about air conditioning technology causes airport services to be less than optimal. Therefore, community service activities are needed to improve these skills. This community service activity aims to increase public knowledge about air conditioning technology. The method of community service is by providing training to the community. At the beginning of the training, the theory and introduction to the components and workings of the air conditioning system were given. Furthermore, they were given practical training using the air conditioning practice module in the Airport Engineering Laboratory of the Palembang Aviation Polytechnic. At the end of the training, an evaluation was carried out both in theory and practice. The results of the evaluation of all participants were declared eligible to carry out air conditioning maintenance. Thus, community service activities were declared successful in increasing the knowledge and skills of the participants. It is hoped that with the increased knowledge and skills of participants, airport services to passengers will increase and the aviation industry in Indonesia will be more advanced